慢性髓性白血病患者达沙替尼相关的肺部不良反应分析 (Zhonghua Xue Ye Xue Za Zhi, 2020)
OBJECTIVE: To explore dasatinib-related pulmonary adverse events in patients with chronic myeloid leukemia（CML）. METHODS: We retrospectively analyzed the incidence of pleural effusion（PE）and pulmonary arterial hypertension（PAH）in patients with CML treated with dasatinib at Peking University People's Hospital from April 2008 to January 2020. RESULTS: A total of 280 patients were collected. The median dasatinib treatment time was 26（1–142）months. Ninety（32.1％）patients developed PE, including 40（44.4％）in grade 1, 44（48.9％）in grade 2, and 6（6.7％）in grade 3. The incidence of PE increased gradually with the prolongation of treatment. The multivariate analysis showed that increasing age（every 10 years, HR＝1.6; P<0.001）, advanced phase when starting dasatinib therapy（HR＝2.2; P＝0.008）, and cardiovascular comorbidity（ies）（HR＝1.9; P＝0.018）were significantly associated with developing PE. The advanced phase when starting dasatinib therapy（HR＝3.4; P＝0.001）, interval from diagnosis to taking TKI for≤6 months（HR＝2.2; P＝0.015）, and dose < 100 mg/d when PE was found（HR＝3.1; P＝0.001）were associated with more severe PE. PE relieved or disappeared after intervention in half of the patients. Among 60 patients with symptoms of cough, chest tightness, and shortness of breath, 49 underwent ultrasonic cardiography; 8（16.3％）had high probability of PAH, approximately 3.5％in all patients; and 6（75.0％）of them had PE. PAH was reversible. There was no difference in the incidences of PE and PAH between branded and Chinese generic dasatinib. CONCLUSION: PE is a common dasatinib-related pulmonary adverse event, and PAH is rare in patients with CML. The identification of individuals with high risk, close monitoring, and timely intervention may help to alleviate PE and PAH.